2021
DOI: 10.1038/s41598-021-87348-y
|View full text |Cite|
|
Sign up to set email alerts
|

Antennal transcriptome sequencing and identification of candidate chemoreceptor proteins from an invasive pest, the American palm weevil, Rhynchophorus palmarum

Abstract: For decades, the American palm weevil (APW), Rhynchophorus palmarum, has been a threat to coconut and oil palm production in the Americas. It has recently spread towards North America, endangering ornamental palms, and the expanding date palm production. Its behavior presents several parallelisms with a closely related species, R. ferrugineus, the red palm weevil (RPW), which is the biggest threat to palms in Asia and Europe. For both species, semiochemicals have been used for management. However, their contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 77 publications
(42 reference statements)
2
42
1
Order By: Relevance
“…Given that Rhynchophorus has a palm borer lifestyle, the damage is based on larvae survivorship in the host palm trunk coupled with late damage and infestation diagnosis [ 17 ]. Thus, understanding the insect’s behavior is important for the implementation of new control strategies, especially those derived from research on telemetry [ 37 ], semiochemical interference [ 38 , 39 , 40 , 41 ], new secondary metabolites and formulations [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], early infestation detection [ 50 ], novel biopesticides [ 51 , 52 , 53 , 54 ], and natural enemies [ 55 , 56 ].…”
Section: The Genus Rhynchophorus Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that Rhynchophorus has a palm borer lifestyle, the damage is based on larvae survivorship in the host palm trunk coupled with late damage and infestation diagnosis [ 17 ]. Thus, understanding the insect’s behavior is important for the implementation of new control strategies, especially those derived from research on telemetry [ 37 ], semiochemical interference [ 38 , 39 , 40 , 41 ], new secondary metabolites and formulations [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], early infestation detection [ 50 ], novel biopesticides [ 51 , 52 , 53 , 54 ], and natural enemies [ 55 , 56 ].…”
Section: The Genus Rhynchophorus Sppmentioning
confidence: 99%
“…Molecular biology has provided some promises [ 39 ], eliciting interest in adopting biotechnological alternatives to pest control, mitigating the damage in different crop pests. The RNAi technique breaks the odor-binding protein, thus preventing the insects from tracking specific semiochemicals [ 38 ].…”
Section: Alternative For Rhynchophorus Palmarum and Rhynchophorus Ferrugineus Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of gustatory receptor genes in R. ferrugineus reported in this study (50 genes encoding 65 functional receptors) is higher than in previous studies, which identified genes from the transcriptomes (9–15 genes) [ 58 , 60 ]. A recent antennal transcriptome study in the American palm weevil, Rhynchophorus palmarum , has identified only seven gustatory receptor genes [ 78 ]. We believe that the transcriptome technique has many limitations in identifying Gr genes.…”
Section: Discussionmentioning
confidence: 99%
“…The genes reported in our study provide additional knowledge on the pool of identified olfactory genes in coleopterans. Compared with a large number of studies on Lepidopteran species, the current understanding of olfactory genes in Coleoptera is mainly sourced from a few reported studies on T. castaneum (Engsontia et al, 2008 ), Megacyllene caryae (Mitchell et al, 2012 ), I. typographus , and D. ponderosae (Andersson et al, 2013 ), Leptinotarsa decemlineata (Liu et al, 2015 ), H. parallela (Yi et al, 2018 ), Rhynchophorus ferrugineus (Antony et al, 2016 ; Gonzalez et al, 2021 ), etc. S. schevyrewi belongs to the genus of bark beetles and shares similar biology with the related species that are destructive forest pests, such as I. typographus and D. ponderosae .…”
Section: Discussionmentioning
confidence: 99%